Improving the biodegradation of chicken feathers by a Bacillus licheniformis ZSZ6 mutant and application of hydrolysate. (May 2023) - Cui, Chunhong; Sun, Liqiong; Chen, Xuelian; Zhu, Yu; Zheng, Zhi; Mao, Dongmei; Li, Mingxu; Li, Yuxin; Cao, Yajun; Feng, Bing; Wang, Hui; Wang, Lin; et al.
Abstract: Microbial degradation of keratin-containing wastes is an eco-friendly and low-cost approach to recycle agricultural byproducts. Bacillus licheniformis has been previously reported as a highly effective feather-degrading bacterium. The aim of the present study was to screen a higher keratinase-yielding mutant by ultraviolet (UV) mutagenesis, assess the effect of hydrolysate on the growth of Chinese cabbage and reveal the changes in the mutant genome. After UV mutagenesis, the UV25-4 mutant was identified as the most efficient mutant. Compared with the ZSZ6 strain, the UV25-4 strain increased the feather degradation rate and the maximum keratinase activity by 25.6% and 110.9%, respectively ( p  < 0.05). The differences were also reflected in the release of total nitrogen and amino acids in the hydrolysates ( p  < 0.05). The hydrolysate of UV25-4 significantly increased the growth and quality of Chinese cabbage in terms of plant height, dry weight, vitamin C, soluble sugar and protein levels ( p  < 0.05). The comparative genomics analysis detected 49 single nucleotide polymorphisms (SNPs) and 19 insertion deletions. The present findings indicated that UV mutagenesis is an effective strategy to obtain efficient feather-degrading strains and that feather hydrolysates may be used as amendments to enhance the growth and quality of vegetables. Highlights: Feather degradation efficiency of Bacillus licheniformis was improved by UV mutagenesis. Hydrolysate of strain UV25-4 improved the growth and quality of Chinese cabbage. UV radiation induced the change of 49 single nucleotide polymorphisms and 19 insertion deletions.